IL‐33/ST2 axis deficiency exacerbates neutrophil‐dominant allergic airway inflammation. Issue 6 (16th June 2021) - Ma, Qiyun; Qian, Yan; Jiang, Jingxian; Wu, Jingjing; Song, Meijuan; Li, Xinyu; Chen, Zhongqi; Wang, Zhengxia; Zhu, Ranran; Sun, Zhixiao; Huang, Mao; Ji, Ningfei; et al.
Abstract: Objective: The IL‐33/ST2 axis has been extensively investigated in type 2 eosinophilic inflammation. Here, we aimed to investigate the role of the IL‐33/ST2 axis in neutrophil‐dominant allergic airway inflammation. Methods: House‐dust mite (HDM) extract and lipopolysaccharide (LPS) were administered to establish a murine model of neutrophil‐dominant allergic airway inflammation. The formation of neutrophilic extracellular traps (NETs) in the lung tissues was demonstrated by immunofluorescence imaging. Mature IL‐33 in bronchoalveolar lavage fluid (BALF) was detected by Western blotting. The neutrophilic chemokine KC produced by bone marrow‐derived macrophages (BMDMs) or primary alveolar epithelial cells was measured with a commercial ELISA kit. Results: In the present study, we observed neutrophilic inflammation and tight junction damage in the lungs of mice sensitised with HDM and LPS. Furthermore, sensitisation with HDM and LPS resulted in the formation of NETs, accompanied by increased levels of mature IL‐33 in the BALF. Moreover, LPS damaged the epithelial tight junction protein occludin directly or indirectly by inducing NET formation. Surprisingly, IL‐33 deficiency augmented neutrophilia and epithelial barrier injury in the lungs of mice after sensitisation with HDM and LPS. Similarly, the absence of ST2 exacerbated the neutrophilic inflammatory response, decreased the expression of occludin and exacerbated the severity of neutrophil‐dominant allergic airway inflammation in an HDM/LPS‐induced mouse model. Mechanistically, BMDMs and alveolar epithelial cells from IL‐33‐ or ST2‐deficient mice tended to produce higher levels of the neutrophilic chemokine KC. Conclusions: These results demonstrated that the IL‐33/ST2 axis may play a protective role in neutrophil‐dominant allergic airway inflammation. Abstract : Most research on the IL‐33/ST2 axis has been conducted in type 2 immunity‐mediated eosinophilic asthma, but less research has focused on neutrophilic asthma. In this study, we found that IL‐33/ST2 axis deficiency aggravated neutrophil‐dominant allergic airway inflammation induced by house‐dust mite and lipopolysaccharide coexposure, which may account for the more proinflammatory status of IL‐33/ST2 axis‐deficient macrophages and lung epithelial cells.